The Influence of Transformational Leadership, Employee Engagement, and Organizational Culture on Innovation Performance - Kristian Hoegh Pride Lambe; Latifa Dinar Rahmani Hakim; Ramdan Yusuf; Eko Meiningsih Susilowati (Malaqbi Publisher, 2026)
Innovation performance has become a critical determinant of organizational competitiveness in increasingly dynamic and uncertain environments. This study investigates the influence of transformational leadership, employee engagement, and organizational culture on innovation performance, with particular emphasis on the mediating role of employee engagement and the moderating role of organizational culture. Using a quantitative, explanatory research design, data were collected through a structured questionnaire from 268 full-time employees across medium and large organizations in innovation-driven sectors. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to test the proposed hypotheses. The results indicate that transformational leadership has a significant positive effect on both employee engagement and innovation performance. Employee engagement is also found to positively influence innovation performance and partially mediates the relationship between transformational leadership and innovation performance. Additionally, organizational culture significantly moderates the relationships between transformational leadership and innovation performance, as well as between employee engagement and innovation performance, such that these relationships are stronger in innovation-supportive cultures. The findings highlight the importance of aligning leadership practices, employee engagement initiatives, and organizational culture to achieve sustainable innovation outcomes. This study contributes to the leadership and innovation literature by offering an integrated empirical framework and provides practical implications for organizations seeking to enhance innovation performance through human and cultural factors.